Public-Private Partnerships in Agriculture Value Chains: The Case of Project ConVERGE in the Philippines - Marife Magno-Ballesteros; Jenica A. Ancheta (Philippine Institute for Development Studies (PIDS), 2022)
This study examines the public-private-producers partnership (4Ps) model for agriculture value chain development implemented through Project ConVERGE of the Department of Agrarian reform. The model adopted a cluster approach whereby farmers groups are organized into clusters to coordinate their production methods to produce good uniform products and other business activities. The interventions or assistance from both government agencies and private sector are coordinated through the Project Management Office of ConVERGE at the central, regional and provincial levels. The study notes that the 4Ps is a form of facilitator driven agriculture value chain that is a suitable strategy given the level of agriculture development in the country. The 4Ps value chain interventions have addressed some of the constraints faced by small farmers to participate in the value chain. Farmer cooperatives that received the interventions specifically on farm equipment and processing facilities reported increased production, expansion of production area, improved mobility and less dependence on traders. However, markets remain limited and the cooperatives still lack the volume and quality of production that is required by major buyers including exporters. The key challenges include the lack of effective extension services including organizational training; inadequate capital and credit access of farmers cooperatives; limited subsidy for infrastructure development and other value chain interventions; weak cooperatives or farmers organizations; and poor geographic conditions. Government plays a major role in addressing these challenges. It needs a coordinated plan among partners agencies for extension and capacity building. Given bureaucratic problems and other institutional constraints, there is also a need to have a good selection of private sector partners both as service providers and financing partners. Markets access can be improved through links with financial institutions and agro-input dealers and through development of brands and certification. In the case of farmers organizations, they need to strengthen their savings and insurance programs to enhance credit access and to hedge against climate shocks.
Keywords: 330; agriculture; public-private partnership; agribusiness; supply chain; agrarian reform